Monitoring Automation System Design Hydroponics Based on Chatbot - Tholib Hariono; Ahmad Chanifuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The development of information technology has had a tremendous impact on human life. The impact is felt in almost all aspects of life, including agriculture. Farming with hydroponic systems has been widely developed, including the role of information technology to improve the quality and efficiency of crop management. A smart hydroponic system was designed to be able to detect and perform actions automatically. Various sensors are installed for multiple needs, such as checking nutrient levels and adding them when nutrients are running out, controlling water ph levels, controlling water temperature, controlling water levels, etc. To optimize this smart hydroponic system, facilities are needed for monitoring data on the system. This research makes monitoring of a hydroponic automation system based on a telegram chatbot. The chatbot can be obtained from the TDS sensor, Ph sensor, water level sensor, and temperature sensor. According to the incoming request, data from each sensor is sent via IoT with the ESP8266 MCU node and Firebased database to the chatbot. This study uses the waterfall software development method. The results showed that monitoring data on the hydroponic automation system could run well with an average time needed to access 1.44 seconds.